Effect of Platelet-Rich Plasma on Differentiation of Osteoblasts and Osteoclasts in the Presence of Three-Dimensional Scaffold - Hadi Mokhtari; Azadeh Montaseri; Ali Mojaddadi; Hamid Reza Mokhtari Zonouzi; Nahid Karimiyan; Saba Arami (Pharmaceutical Sciences, 2018)
Background: Osteoblasts’ activity is prerequisite for prevention from and treatment of apical periodontitis and a relatively high proportion of endodontically treated teeth will require retrograde treatment in future. Therefore, the aim of the present study was to evaluate the effect of platelet-rich plasma (PRP) on differentiation of stem cells into osteoblasts and osteoclasts. Methods: Mesenchymal stem cells were isolated from human fetal umbilical cord and cultured on two polycaprolacton/hydroxyapatite (PCL/HA) polymer scaffolds. In addition to differentiation agents, 10% PRP was added to PRP containing subgroups. After 10 days, osteoblast differentiation was assessed evaluating the osteocalcin and osterix gene levels where, in the osteoclast differentiation group the expression of tartarate-resistant acid phosphatase (TRAP) gene was evaluated. Results: Expression of TRAP gene did not reveal any significant differences between the study and control groups. There was a significant difference in osterix expression between the control and the PRP-treated groups (p < 0.01) as well as osteocalcin gene (p < 0.05). Conclusion: The results showed that PRP increased the osteoblastic differentiation, while it does not cause any significant increase in osteoclastic differentiation.